The Warthin-Like Variant of Papillary Thyroid Carcinoma: A Comparison with Classic Type in the Patients with Coexisting Hashimoto’s Thyroiditis - Min-kyung Yeo; Ja Seong Bae; Sohee Lee; Min-Hee Kim; Dong-Jun Lim; Youn Soo Lee; Chan Kwon Jung (International Journal of Endocrinology)
Background. The Warthin-like variant of papillary thyroid (WLPTC) is a rare subtype of papillary thyroid carcinoma (PTC) resembling Warthin tumors of the salivary glands. Due to its rarity, the clinicopathologic and molecular features of WLPTC remain unclear. Methods. Of the 2,139 patients who underwent surgical treatment for PTC from 2012 to 2013, 40 patients with WLPTC were identified and compared to 200 consecutive patients with classic PTC. BRAF mutation was tested with pyrosequencing. Results. There were no significant differences in age, predilection for women, multifocality, extrathyroidal extension, or lymph node metastasis between WLPTC and classic PTC. However, WLPTCs were more commonly associated with Hashimoto’s thyroiditis than classic PTCs (93% versus 36%, resp., P < 0.001) and showed significantly lower rate of BRAF mutation when compared to classic PTCs (65% versus 84%, resp., P = 0.007). In classic PTC, the frequency of BRAF mutations was negatively correlated with coexisting Hashimoto’s thyroiditis. When we compared WLPTC and classic PTC in the patients with coexisting Hashimoto’s thyroiditis, there were no significant differences in clinicopathologic characteristics or the BRAF mutational rate between the two groups. Conclusions. Patients with WLPTC have similar demographic, clinical, pathologic, and molecular characteristics to those with classic PTC coexisting with Hashimoto’s thyroiditis.